Investigation of Building Walls Exposed to Periodic Heat Transfer Conditions for Green and Energy Efficient Building Construction. (2016) - Shaik, Saboor; Gorantla, Kiran Kumar; Setty, Ashok Babu Talanki Puttaranga
Abstract: Buildings account for about 40% of total electricity use in the world for artificial cooling and artificial day lighting and they are also responsible for 40% CO2 emissions. This work reports a comprehensive investigation of thermal performance characteristics which include thermal transmittance, thermal admittance, decrement factor and the time lag for both homogeneous and composite building walls. A computer program with the cyclic admittance method was developed to study unsteady thermal performance characteristics. The Five building materials such as, cellular concrete, mud brick, concrete block, burnt brick and fly ash bricks were selected for the study. The heat transfer characteristics of five homogeneous building walls and their five composite walls were studied in detail. From the results, it is observed that fly ash brick homogeneous walls and their composite walls are energy efficient from the lowest decrement factor and the highest time lag perspective among five homogeneous and five composite walls studied. The decrement factor and time lag values of homogeneous fly ash bricks were observed to be 0.401 and 8.159 h, respectively, whereas the values of composite fly ash brick walls were observed to be 0.342 and 9.199 h, respectively.